Perancangan Prototipe Aplikasi Pembelajaran Sains dan Matematika untuk Siswa SMK Menggunakan Design Thinking - Farah Akmalia Maylani; Mukhlis Ainur Rahman; Fadli Maghfirli (Journal of Progressive Science Education, 2025)
The development of digital technology demands learning innovations that can meet the needs of students in the era of the Fourth Industrial Revolution and Society 5.0. In the context of vocational high schools (SMK), science and mathematics are often taught only theoretically and lack context, making it difficult for students to connect theoretical concepts with vocational practices. This study aims to design a prototype of a science and mathematics-based mobile learning application for vocational high school students using the Design Thinking approach. This method consists of five stages, namely empathize, define, ideate, prototype, and testing, which emphasize active user involvement. The trial was conducted on twenty-two vocational high school students in Bangkalan using the User Experience Questionnaire (UEQ) instrument. The results of the UEQ test obtained an attractiveness score of 2.583, a clarity score of 1.943, an efficiency score of 2.352, an accuracy score of 2.364, a stimulation score of 2.284, and a novelty score of 1.995. Based on these scores, positive results were obtained in all aspects of the UEQ.